Child psychopathology from infancy to adolescence - Schneider, Barry; Hastings, Paul D.; Guyer, Amanda; Brendgen, Mara; Cwinn, Eli (New York Cambridge University Press, 2015)
"This textbook covers the classification, causes, treatment and prevention of psychological disorders in the infant through the adolescent years. Chapters balance the social and historical context of psychopathology with the physiological roots of abnormal behavior, leading students to a comprehensive understanding of child psychopathology. The book is totally up-to-date, including coverage of the DSM-5 and criticisms of it. In four parts, this textbook describes the empirical bases of child psychopathology as well as the practice of child psychologists, outlining the classification and causes of disorders in addition to methods of assessment, intervention and treatment"--Provided by publisher.
Keywords: Child psychopathology; Child psychiatry